2017
DOI: 10.23887/ijll.v1i1.9612
|View full text |Cite
|
Sign up to set email alerts
|

ERRORS ANALYSIS IN SHORT BIOGRAPHY TEXT WRITTEN BY THE 11th GRADE STUDENTS OF A VOCATIONAL HIGH SCHOOL IN SINGARAJA

Abstract: This study was a descriptive qualitative study aimed at analysing types of error and sources of error in the short biography text writings in English language teaching (ELT) context. The subject of this study was 11 th Grade of Accounting Department Students of a Vocational High School in Singaraja in the academic year 2015/2016. The instruments in the study were researcher, tabulation table, and interview guide. The textual analysis design was used in this study to gather the data. The students' errors were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 1 publication
(1 reference statement)
0
16
0
Order By: Relevance
“…As mentioned by Gustilo and Magno (2015) that writing in a second and foreign language is difficult; it is proven by the quality of the second language writing by the students is lowest than their first language writing. Moreover, Suwastini and Yukti (2017) mention that writing is very complicated because it involves the need to write grammatically so that these expressions can be understood for Indonesian students who learn English as a foreign language (EFL).…”
Section: Doimentioning
confidence: 99%
“…As mentioned by Gustilo and Magno (2015) that writing in a second and foreign language is difficult; it is proven by the quality of the second language writing by the students is lowest than their first language writing. Moreover, Suwastini and Yukti (2017) mention that writing is very complicated because it involves the need to write grammatically so that these expressions can be understood for Indonesian students who learn English as a foreign language (EFL).…”
Section: Doimentioning
confidence: 99%
“…Budiarta, Suputra, and Widiasmara (2018) found that the difference between grammatical rules of target language languages and native language was the main cause for students' errors (Budiarta et al, 2018). Meanwhile, Suwastini and Yukti (2017) identified interlingual transfer as the dominant cause of of the students' grammatical errors among the students' short biography texts that they observed. In addition, the students often translate their ideas from native language to target language in composing writing ( Isa, Risdaneva and Alfayed (2017)).…”
Section: Introductionmentioning
confidence: 97%
“…However, grammatical errors still become an important problem in writing, especially for EFL students. Suwastini and Yukti (2017) for example were concerned with the errors committed by students learning English as Foreign Language in a vocational school in Bali and revealed that misformation and omission were the most common type of error committed in the students' short-biography writing that they result. Very similar result was found by Megantari and Budasi (2018) who observed the grammatical errors in vocational school students' narrative text, and revealed that misinformation and omission were committed most frequently by the students.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations